Model-free stochastic collocation for an arbitrage-free implied volatility, part II - Fabien Le Floc'h; Cornelis Willebrordus Oosterlee (Risks, 2019)
This paper explores the stochastic collocation technique, applied on a monotonic spline, as an arbitrage-free and model-free interpolation of implied volatilities. We explore various spline formulations, including B-spline representations. We explain how to calibrate the different representations against market option prices, detail how to smooth out the market quotes, and choose a proper initial guess. The technique is then applied to concrete market options and the stability of the different approaches is analyzed. Finally, we consider a challenging example where convex spline interpolations lead to oscillations in the implied volatility and compare the spline collocation results with those obtained through arbitrage-free interpolation technique of Andreasen and Huge.
Keywords: 330; stochastic collocation; implied volatility; quantitative finance; arbitrage-free; risk neutral density; B-spline